Optical coherence tomography of re-pressurised porcine coronary arteries: A systematic study. (March 2016) - Adnan, Asif; Robinson, Claire; Biggs, Mike; Joseph, Shiju; Morgan, Bruno; Rutty, Guy; Adlam, David
Abstract: Cardiovascular death is the most frequently reported cause of adult natural death in autopsy reports in the UK. However, the approach used for diagnosing coronary artery disease at autopsy is largely based on visual assessment of coronary artery cross sections to determine the severity of stenosis. This is subject to criticism and heterogeneity. Objective: We investigated the potential role of a novel intravascular imaging technique, optical coherence tomography (OCT), in post-mortem diagnosis of coronary artery disease and what effect re-pressurisation has on vessel dimensions, as measured by OCT. Our long term aim is to investigate the role of OCT as a minimally invasive autopsy tool. Materials and methods: We used several ex-vivo porcine hearts to develop the techniques. Subsequently, 6 coronary arteries were used for detailed experiments. Vessels were gradually re-pressurised using normal saline and clinical coronary pressure wire and OCT systems were used for recording the pressure and intracoronary imaging. Results: Our data showed re-pressurisation significantly alters the vessel dimensions. The mean cross sectional area increased from 3.3 to 8.4 mm 2 proximally and from 2.5 to 7.4 mm 2 distally. Conclusion: We conclude that OCT in the ex-vivo setting is feasible and re-pressurisation significantly alters vascular dimensions. This implies, there might be significant discrepancies between the true severities of stenosis in life and that which is determined by visual estimation during autopsy in the collapsed vessels. OCT of re-pressurised vessel can overcome this issue and has the potential to improve the accuracy of post-mortem assessment of coronary artery disease. Highlights: Assessment of coronary artery disease during conventional autopsy has several limitations. Optical coherence tomography (OCT) can address some of these issues due very high resolution. OCT of re-pressurized post-mortme vessels show significant change in vessel size Cadaveric translation of the findings may be crucial for minimally invasive autopsy.